A new approach to correlate the defect population with the fatigue life of selective laser melted Ti-6Al-4V alloy. (July 2020) - Hu, Y.N.; Wu, S.C.; Wu, Z.K.; Zhong, X.L.; Ahmed, S.; Karabal, S.; Xiao, X.H.; Zhang, H.O.; Withers, P.J.
Highlights: The predominant failure is from near surface defects rather than the α′ phases. The fatigue limit is predicted by the statistics of extreme and the Murakami model. The Kitagawa-Takahashi diagram is extended to the finite life region. The safe (infinite) life region is reformulated by the Chapetti model. Abstract: Microstructural features and defects arising from selective laser melting (SLM) determine the in-service performance of additively manufactured near-net-shape components. Here the grain type, shape, size and distribution were characterized using electron backscattered diffraction (EBSD). High-resolution synchrotron radiation X-ray computed tomography (CT) was used to quantify the population, morphology and dimensions of porosity and lack of fusion defects. For SLM Ti-6Al-4V alloy, the larger-sized defects in comparison with the α grains are more important for crack initiation, typically leading to poor fatigue resistance and a pronounced variation in fatigue life. The fatigue strength was then evaluated in terms of the defect population using a combination of the statistics of extremes and the Murakami model. Finally, an extended Kitagawa-Takahashi fatigue diagram was established within the framework of defect-tolerant design, which includes a classical safe-life region and the defect-determined lifetime in the finite life region.